LEVEL OF SOCIAL CONFLICT POTENTIAL IN KAZAKHSTAN: POSSIBLE RISKS AND THREATS - NASIMOVA, Gulnar (CENTRAL ASIA AND THE CAUCASUS, 2011)
As world experience shows, countries that embark on the path of socioeconomic and political modernization are likely to encounter a rise in social tension and the emergence of numerous conflicts. The Republic of Kazakhstan is well versed in the prevention of these phenomena. Nevertheless, modernization in Kazakhstan is bringing to the fore other problems relating to efficient conflict management and finding peaceful constitutionally legal ways to carry out comprehensive reform of society. It is a well-known fact that the aggravation of contradictions and the political conflicts in the post-Soviet states, which in some cases have led to armed conflicts, are undoubtedly related both to historical prerequisites and to crisis phenomena in the development of the sociocultural, socioeconomic, and political spheres of public relations. However, we think that one of the main reasons for the emergence of the domestic political conflicts in the CIS countries has been the poor development of ways to prevent and regulate them. So strategies and efficient mechanisms must be sought for taking preventive measures against possible social upheavals and the outbreak of conflict action and for reaching a consensus among the political entities. It goes without saying that an entirely conflict-free society with ideal social relations is a utopia. Institutionalized conflicts are a different matter however, since they potentially perform a constructive function and help society to progress. The author of this article concentrates on potentially destructive conflicts, the settlement of which could be accompanied by social upheavals.